Кінобалада або про “повернення, що тривають нескiнченно” - Рутковська, Т. (Студії мистецтвознавчі, 2008)
The article analyses Henryk Kluba’s film “The Sun Rises Once a Day” produced after a short story by Wiesław Dymny. The Author claims that the film ranks among film ballads and its structure coincides with the folk ballad scheme assumed in folklore analysis, whereas its main protagonist bears all the features typical of a folk ballad character. All these, as well as the visual facet of the film allow one to consider it to be one of the rare works in Polish cinema deeply rooted in native folklore. The only discord observed is the final scene forced by the censors, as it contradicts structural principles of a ballad. Made in 1968, the film was shown in cinemas only briefly in 1972, and more general public could see it only at the end of the 1980s, well after its times. The same happened to many films in the period.